The illness of women and men with sickle cell disease: a Grounded Theory study - Rosa Cândida Cordeiro; Silvia Lúcia Ferreira; Ane Caroline da Cruz Santos (Universidade de São Paulo, 2015)
Objective: to understand the meanings given by women and men with sickle cell disease on the illness experience. Method: analytical study with a qualitative approach, conducted with 17 adults with sickle cell disease using the Theory Based on Data, or Grounded Theory, as theoretical-methodological referential. Data were collected between the years of 2012 and 2013, in an individual in-depth interview. All the interviews were recorded and analyzed according to the Grounded Theory comparative analysis technique. Results: data show four categories which group the experience of illness, the feelings experienced and the path to living with sickle cell disease. Conclusions: it was possible to understand that the experience was built by a process in which these people redefined the meaning of their lives, applying new directions to life and to care regarding the experience of the illness. In the context of chronic disease, the nurse's care is also seen in this study as a foundation, providing attention, directions, and guidance through the required confrontations. Understanding the experience lived by these people, it is possible to enlarge the dimensions and the essence of nursing care required throughout life.